Determinants of International Migration: Empirical Evidence for Migration from Developing Countries to Germany - Ralph Rotte; Michael Vogler (Institute for the Study of Labor (IZA), 1998)
By means of a descriptive survey of theoretical literature the paper first works out the potential determinants that may drive international migration from developing to developed countries. Furthermore, we look on the relationship between trade, development and migration. Empirical studies focusing on international migration from LDCs so far are very scarce. The paper utilizes a new dataset that is based on migration from 86 African and Asian countries to Germany. Information is available on overall moves (1981-1995) and asylum migration (1984-1995). The estimation results confirm the importance of the economic differential between countries for migration, the existence of an inverse u-shaped relationship between development and migration, as well as the importance of the political situation in sending countries and of network effects.
Keywords: O19; O15; F22; 330; migration; international migration; developing countries; Internationale Wanderung; Schätzung; Entwicklungsländer; Deutschland